Peran Masyarakat Dalam Penanggulangan Tindak Pidana Korupsi - Fauzi, Muhammad; , Sudaryono, SH., M.Hum; , Bambang Sukoco S.H.,M.H (2016)
The role of society in the fight against corruption has been set out in Article 41 and 42 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the eradication of corruption. Community participation in tackling corruption manifested in the form of, among others, to seek, obtain, provide data or information about corruption and the right advices and opinions are responsible for the prevention and eradication of corruption. which further regulated in Government Regulation No. 71 Year 2000 on the Implementation of Public Participation and the Award in the Prevention and Combating of Corruption. From these results, many ways to do community participate in tackling corruption like, as well as through the whistle-blower role, Justice Collaborators, media, activities directly and through anti-corruption education. This type of research is a kind of normative legal research. The conclusion of this study is the need for efforts to strengthen the community in understanding the problem of corruption so that people participate more and can produce a quality report on the allegations of corruption.